PENGARUH PRESTASI KERJA DAN KOMPETENSI KARYAWAN TERHADAP PROMOSI JABATAN PADA INNA SINDHU BEACH HOTEL SANUR, DENPASAR - Sasmita, Ida Ayu Gita Dwi; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 5 No 8 (2016), 2016)
The implementation of the promotion is done too subjective, where there's injustice in promoting employee is not the person who according to the experts, but people close to the boss. This gives rise to envy among employees. This study aims to determine the effect of work performance and competence of employees against promotion at Inna Sindhu Beach Hotel. This research was conducted at the Inna Sindhu Beach Hotel Sanur,  Denpasar. The population in this study as many as 79 people, consisting of 53 permanent employees and 26 contract employees. This study uses the Achievement Motivation Theory of David C. McClelland and sampling method saturated because uses all permanent employees as respondents. The analysis technique used is multiple linear regression analysis. F test results indicate that the performance and competence affect the promotion is the appropriate model. T test results showed that job performance and significant positive effect on the promotion of employees is 2,385. Competence positive and significant impact on the promotion of 2.254. Values ??of significance below 0.05. The advice that can be given is preferably employees can accomplish a task in accordance with the time limits set and tops provide opportunities for promotion to employees who have a loyalty to the company, while the things that need to be preserved is the condition of the workspace that can lead to comfort employees in the works.
Keywords: Performance, Competency, Promotion